2023
DOI: 10.3389/fnut.2022.1007725
|View full text |Cite
|
Sign up to set email alerts
|

The association between vitamin D status and inflammatory bowel disease among children and adolescents: A systematic review and meta-analysis

Abstract: AimVitamin D deficiency is very common among children with IBD. Since there are conflicting results regarding the association of vitamin D with IBD, we conducted this systematic review to confirm the association of vitamin D with IBD.MethodsWe conducted a systematic search in Scopus, Cochrane Library, Web of Science, PubMed, and Google Scholar to find relevant studies. Articles with cross-sectional and case-control designs that reported the association between vitamin D and IBD among children were included.Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…show that patients with IBD and especially CD also show a low vitamin D status and indicate a correlation with disease activity. Unfortunately, disentangling causality and correlation is an unresolved challenge in the ongoing debate about the interplay between Vitamin D and IBD [36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…show that patients with IBD and especially CD also show a low vitamin D status and indicate a correlation with disease activity. Unfortunately, disentangling causality and correlation is an unresolved challenge in the ongoing debate about the interplay between Vitamin D and IBD [36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…Suboptimal concentrations of vitamin D negatively affect the epithelial barrier and immune functions and lead to increased dysbiosis and possible translocation of intestinal bacteria, thereby influencing the onset and progression of IBD [ 9 , 10 ]. Vitamin D deficiency is common in IBD patients [ 10 , 11 ], but some studies also reported a lack of decrease in vitamin D levels in these patients [ 12 , 13 ]. There are also different results in children with IBD pointing to an association between IBD severity, activity, therapeutic control and vitamin D levels [ 11 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin D deficiency is common in IBD patients [ 10 , 11 ], but some studies also reported a lack of decrease in vitamin D levels in these patients [ 12 , 13 ]. There are also different results in children with IBD pointing to an association between IBD severity, activity, therapeutic control and vitamin D levels [ 11 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the field of IBD research, it was found that vitamin D deficiency was associated with IBD ( 7 ). Vitamin D is a lipophilic compound synthesized in the skin under the sun, and it is hydroxylated to 25-hydroxyvitamin D [25(OH)D] in the liver and further hydroxylated in the kidneys to 1,25-dihydroxyvitamin D [1,25(OH)2D], which is the active metabolite ( 8 ).…”
Section: Introductionmentioning
confidence: 99%